2022
DOI: 10.3904/kjim.2020.685
|View full text |Cite
|
Sign up to set email alerts
|

Reference diameter and characteristics of the distal radial artery based on ultrasonographic assessment

Abstract: Background/Aims: While distal radial artery (DRA) access is increasingly being used for diagnostic coronary angiography, limited information is available regarding DRA size. We aimed to determine the DRA reference diameters of Korean patients and identify the predictors of DRA diameter < 2.3 mm.Methods: The outer bilateral DRA diameters were assessed using a linear ultrasound probe in 1,162 consecutive patients who underwent transthoracic echocardiography. The DRA diameter was measured by the perpendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“… 14 One study showed that a low body mass index (BMI) and a low body surface area were significant predictors of a DRA diameter <2.3 mm. 15 BMI was significantly correlated with DRA diameter (r = 0.66, P < 0.0001) in a Japanese study of 142 patients. 16 However, another Japanese study did not report an association between vessel diameter and clinical variables, including BMI, in multivariate analysis.…”
Section: Discussionmentioning
confidence: 89%
“… 14 One study showed that a low body mass index (BMI) and a low body surface area were significant predictors of a DRA diameter <2.3 mm. 15 BMI was significantly correlated with DRA diameter (r = 0.66, P < 0.0001) in a Japanese study of 142 patients. 16 However, another Japanese study did not report an association between vessel diameter and clinical variables, including BMI, in multivariate analysis.…”
Section: Discussionmentioning
confidence: 89%
“…Based on previously published data (10,11) , there are about five factors--gender, height, weight, BMI, BSA--related to the diameter of the distal radial artery. We calculated an effective sample size according to 10 events per independent variable principle (12) .…”
Section: Discussionmentioning
confidence: 99%
“…There may be differences in the diameter of the distal radial artery in different population. In the PubMed database, we retrieved 10 articles that had published before 14 February 2022 and had reported the diameter of the distal radial artery by ultrasound measurement (6,10,11,(13)(14)(15)(16)(17)(18)(19) , Table 3. As we can see from the table, the diameter of the distal radial artery ranges from 1.70 +-0.5mm to 2.99 +-0.60mm.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the distal radial artery is approximately 80%-90% smaller than that of the forearm radial artery, and that of females is smaller than that of males. 23,24) Therefore, a smaller puncture needle (20-22 G) and guidewire (0.018-0.025") are useful in increasing the success rate. Ultrasound-guided puncture, although requiring a learning curve, will also increase the success rate compared with palpation-guided puncture.…”
Section: Fig 4 Pre-(a) and Post-embolization (B) Of The Aneurysmmentioning
confidence: 99%